Physicians’ Perceptions of Electronic Prescribing with Electronic Medical Records in Kuwaiti Primary Healthcare Centres - Bashair A. Almutairi; Henry W. W. Potts; Saadoun F. Al-Azmi (Sultan Qaboos University Medical Journal, 2019)
Objectives: This study aimed to evaluate physicians’ perceptions of electronic prescribing in Kuwaiti primary healthcare centres. Methods: This cross-sectional study was conducted between June and August 2017 among 368 physicians from 25 primary healthcare centres in Kuwait. Data were collected from the participants using a self-reported questionnaire, including sociodemographic characteristics, previous experience with computers and awareness, knowledge and use of e-prescribing systems and their functional features. In addition, perceptions of the benefits and levels of satisfaction associated with e-prescribing were explored. Results: A total of 306 physicians completed the survey (response rate: 83%). The majority had positive perceptions regarding the use of e-prescribing, particularly in terms of time-savings (86%), healthcare quality (84%), productivity (80%) and clinical workflow and efficiency (83%). However, many respondents indicated that e-prescribing systems required additional improvements in terms of functionality. Conclusion: Most physicians in primary healthcare centres in Kuwait recognised the importance of e-prescribing to improve the quality of patient care, streamline workflow, increase productivity and reduce medical errors. However, there is a need to improve the design and infrastructure of e-prescribing systems, which may aid in the adoption of such systems in Kuwait.